Solar Thermoplasmonic Nanofurnace for High-Temperature Heterogeneous Catalysis - Naldoni, Alberto; Kudyshev, Zhaxylyk A; Mascaretti, Luca; Sarmah, Smritakshi P; Rej, Sourav; Froning, Jens P; Tomanec, Ondřej; Yoo, Jeong Eun; Wang, Di; Kment, Štěpán; Montini, Tiziano; Fornasiero, Paolo; et al. (Nano letters, 2020)
Most of existing solar thermal technologies require highly concentrated solar power to operate in the temperature range 300-600 °C. Here, thin films of refractory plasmonic TiN cylindrical nanocavities manufactured via flexible and scalable process are presented. The fabricated TiN films show polarization-insensitive 95% broadband absorption in the visible and near-infrared spectral ranges and act as plasmonic "nanofurnaces" capable of reaching temperatures above 600 °C under moderately concentrated solar irradiation (∼20 Suns). The demonstrated structures can be used to control nanometer-scale chemistry with zeptoliter (10-21 L) volumetric precision, catalyzing C-C bond formation and melting inorganic deposits. Also shown is the possibility to perform solar thermal CO oxidation at rates of 16 mol h-1 m-2 and with a solar-to-heat thermoplasmonic efficiency of 63%. Access to scalable, cost-effective refractory plasmonic nanofurnaces opens the way to the development of modular solar thermal devices for sustainable catalytic processes.
Keywords: titanium nitride; sustainable catalysis; nanocavity; solar chemicals; solar-thermal; plasmonics